Family for beginners - Morgan, Sarah, 1948- (HQN, 2020)
"New York florist Flora Donovan is living the dream, but her bubbly optimism hides a secret. She's lonely. Orphaned as a child, she's never felt like she's belonged anywhere... until she meets Jack Parker. He's the first man to ever really see her, and it's life changing. Teenager Izzy Parker is holding it together by her fingertips. Since her mother passed away a year ago, looking after her dad and little sister is the only thing that makes Izzy feel safe. Discovering her father has a new girlfriend is her worst nightmare - she is not in the market for a replacement mom. Then her father invites Flora on their summer vacation...Flora's heart aches for Izzy, but she badly wants her relationship with Jack to work. As the summer unfolds, Flora must push her own boundaries to discover parts of herself she never knew existed - and to find the family she's always wanted."--Publisher.